2023
DOI: 10.3390/pathogens12091101
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Profiles and Virulence Determinants in Biofilm-Forming Enterococcus faecium Isolated from Raw Seafood in Bangladesh

Md. Ashek Ullah,
Md. Saiful Islam,
Md. Liton Rana
et al.

Abstract: Pathogenic, antibiotic-resistant, and biofilm-forming bacteria can be transferred to humans through the consumption of contaminated seafood. The present study was carried out to determine antibiotic resistance profiles and virulence determinants in biofilm-forming Enterococcus faecium isolated from seafood in Bangladesh. A total of 150 seafood samples, including shrimp (n = 50), crabs (n = 25), and marine fish (n = 75), were screened using cultural, staining, biochemical, polymerase chain reaction (PCR), Congo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Furthermore, several studies have indicated that shrimp is a carrier of antibiotic-resistant bacteria [ 6 , 7 ]. Antibiotic resistance genes present in multidrug-resistant (MDR) bacteria within shrimp can disseminate through horizontal gene transfer, potentially reaching pathogenic bacteria [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have indicated that shrimp is a carrier of antibiotic-resistant bacteria [ 6 , 7 ]. Antibiotic resistance genes present in multidrug-resistant (MDR) bacteria within shrimp can disseminate through horizontal gene transfer, potentially reaching pathogenic bacteria [ 8 ].…”
Section: Introductionmentioning
confidence: 99%